Analysis of strategies executed by Miramar´s High School Teachers and Staff, from the Regional Board of Education of Puntarenas, Costa Rica, to Prevent Desertion and Students Population Retention - Ovares Elizondo, Rodolfo (2012)
This article analyzes the dropout as the scourge affecting today’s society, while causing significant losses and, over time, widens social gaps as a result of dropping out of school by the student population. Thus we developed a descriptive research supported with quantitative and qualitative techniques in the Liceo de Miramar de Puntarenas, to analyze strategies dropout prevention and student retention, from the perspective of faculty and staff.The study aims to determine the factors causing dropout, the strategies employed by faculty and staff from the management of education and perception of the efficiency and effectiveness of those actions for dropout prevention and student retention in school. Also generate a commitment from the education community to work together on this phenomenon in Costa Rican education.